The Economies of olive plantation, production and processing in The Syrian coast (Economic feasibility of an olive oil press) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
Olive plantation is one of the most common tree plantations in the Syrian coast, and it covers the biggest percentage of cultivable lands in it. This study focuses on this plantation, its spread and expansion horizontally and vertically, since it has many forward and backward linkages with other sectors, especially food industries. And it also focuses on marketing aspects and problems which face this sector concerning price and quality in home and abroad to make it more accessible to foreign markets and to increase its exports and foreign exchange earnings. The study concludes that it is necessary to invest in developing the production, processing and marketing of olive and its oil, and to launch a trade mark to promote this vital product. اقتصادية زراعة وإنتاج الزيتون وتصنيعه في الساحل السوري (الجدوى الاقتصادية لمعصرة زيتون) تعد زراعة الزيتون من أكثر الزراعات الشجرية انتشاراً في الساحل السوري, كما أنّ زراعته تشكل النسبة الأكبر من مساحة الأراضي الصالحة للزراعة. وقد ركز البحث على الاهتمام بهذه الزراعة وانتشارها وتوسعها أفقياً ورأسياً, لما لهذا القطاع من ترابطات أمامية وخلفية مع القطاعات الأخرى وخاصة بالنسبة للصناعات الغذائية. كما تمّ التركيز على النواحي التسويقية والمشاكل التي يتعرض لها داخلياً وخارجياً من حيث الجودة والسعر, وذلك من أجل إمكانية النفاذ إلى الأسواق الخارجية وزيادة التصدير وتحقيق عائداً من العملة الصعبة, وضرورة القيام بالاستثمارات اللازمة لتطوير الإنتاج والتصنيع والتسويق, وتوفير قاعدة بيانات عن الزيتون وزيت الزيتون على شبكة الانترنت ووضع علامة تجارية للتعريف بهذا المنتج الحيوي. إنّ زراعة الزيتون وإنتاجه وتصنيعه في سورية بشكل عام وفي الساحل السوري بشكل خاص ذات أهمية اقتصادية واجتماعية وبيئية وثقافية هامة على المستوى المحلي والوطني, ويمكنه توفير العديد من فرص العمل, وأن يساهم مساهمة فعالة في الناتج المحلي والقومي.